Analisis Efisiensi Penurunan Kadar Logam Berat Pb dan Cu Menggunakan Adsorben Cangkang Kerang Darah - Mutia Chantika Putri; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Shipyards are often criticised for the liquid waste they produce, which has the potential to contaminate marine waters. This research aims to analyse the effectiveness of chitosan from blood clam shells as an adsorbent to reduce the levels of lead and copper in shipyard liquid waste. The research technique uses a batch system. The materials used include both commercial and non-commercial blood clam shell adsorbents. The non-commercial blood clam waste was collected from a fish auction site in Kalanganyar village, Sidoarjo. The concentrations of lead and copper in the wastewater samples were 2.04 and 1.16 mg/L, respectively. Variations in the adsorption stirring speed (90, 100, 110 and 120 rpm) and the amount of commercial and non-commercial blood clam shell adsorbent added to the wastewater samples (0.5; 1; 1.5; and 2 grams) were tested. Measurements were then performed using atomic absorption spectroscopy (AAS). At final concentrations of 0.150 mg/L and 0.144 mg/L, the research results show that the commercial adsorbent with a mass of 2.0 grams and a stirring speed of 110 rpm was able to absorb Pb and Cu metals at 92.65% and 87.58% respectively, while the non-commercial adsorbent with a mass of 2.0 grams and a stirring speed of 110 rpm was able to absorb Pb and Cu metals at 91.81% and 82.31% respectively.